Meningkatkan Prestasi Belajar Siswa dengan Menggunakan Media Powerpoint pada Pelajaran Ilmu Pengetahuan Sosial - Sumarni, Enny (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to improve student achievement during online learning in social studies lessons using Powerpoint media at SMP Negeri 2 Telukjambe Timur, Karawang Regency, West Java Province. This research was conducted in class VIIA SMP Negeri 2 Telukjambe Timur. This research was carried out in two cycles, each cycle consisting of two online meetings. The 1st cycle was held from 04 to 11 August 2020, and the 2nd cycle was held from 18 to 25 August 2020. Qualitative data collection techniques were obtained from observing students' attendance and activeness in learning. The quantitative data that records students' absorption of learning is collected through the implementation of written evaluations with the help of essay questions. Based on the results of the pre-test, it was stated that out of 41 students there were around 68.29% or 28 students who had not finished their studies, while 34.71% or 13 students had completed their studies. When viewed from the achievement of teaching and learning, out of 41 students 68.29% or around 25 grades were still below the teaching and learning process, 19.51% or 8 students had achieved the teaching learning process, and 12.20% or 5 students scored above the teaching learning process. So that from the results of the social studies subject pretest the results can be categorized as still very low. In cycle 1 it can be stated that out of 41 students there were around 19.51% or 8 students who had not completed their studies, while 80.49% or 33 students had completed their studies. When viewed from the achievement of teaching and learning, out of 41 students 19.51% or around 8 grades were still below the teaching and learning process, 60.98% or 25 students had achieved the teaching and learning process, and 19.51% or 8 students scored above the teaching learning process. So that from the results of cycle 1 regarding social interaction material the results can be categorized as low. In the 2nd cycle all students can master this material as proven by 41 students 100% or 41 students have completed their studies. If we look at the achievement of the teaching and learning process, out of 41 students 43.90% or 18 students have achieved the teaching and learning process, and 56.10% or 23 students scored above the teaching and learning process. In this case the treatment in cycle 2 can improve student achievement in social studies subjects which are in the high category.